Estudo da relação entre sucção, dilatância e resistência ao arrancamento de interfaces areia-geossintético - Rodriguez, Maria Gabriela Guevara (2018)
The interface behavior between soil and geosynthetics plays a key role in reinforced soil structures. The soil-geosynthetic interface resistance, usually obtained by pullout or direct shear tests, is an essential parameter for design analysis, whose effect of particle shape and size, soil moisture content and normal stress are very important influential factors. In the case of sandy soils, there is a variation of volume during the mobilization of the friction; the dilatancy and the type of geosynthetics used as reinforcement are the factors that can influence the resistance behavior. Also, under high humidity conditions, soil suction and dilatation in sandy soils become interdependent parameters that may affect interface resistance. This study is based on pullout tests performed with two different types of geosynthetics, being a geogrid and a woven geotextile, which were embedded in a well graded compacted sand with a relative density of 90% under different humidity conditions. The interface dilatation and pullout strength of geosynthetics in sand were studied for the purpose of matrix suction changes during the friction mobilization. For this, a small scale equipment was used, with instrumentation that allowed to register the pulling force, internal displacements of the geosynthetics, displacement of the actuator, vertical displacements and also the suction. The sand was compacted with three different moisture contents: air dry, optimum moisture content of the Proctor Normal curve and saturated. The results showed that the dilatation developed in sand-geogrid interfaces is significant and often bigger than the soil itself. The fabric geotextiles showed, on the other hand, a compression effect on all developed interfaces. It was verified that the high interface dilatation of the sand in the compact state and optimal moisture during geogrid pullout resulted in a decrease in suction but an increase in interface resistance. On the other hand, for compacted sand in the dry state, but at the same relative density, the resistance showed to be lower in comparison with wet sand, showing that the associated effects of capillarity and dilatation are significant in the soil-geosynthetic interface resistance.